Association between Club Sports Participation and Physical Fitness of 6-10-Year-Old Macedonian Children - Besnik Morina; Malsor Gjonbalaj; Seryozha Gontarev; Georgi Georgiev (OVS LLC, 2022)
Background. Physical inactivity is associated with poor physical fitness and weight gain. Organized sports activities can be a significant component in providing adequate fitness which, on its part, is an important aspect of general health and well-being. The purpose of the study was to establish the relationship between participation in organized sports activity and obesity as well as physical fitness of 6-10-year-old children from the region of the city of Skopje in the Republic of North Macedonia. Materials and methods. The height, weight, body mass composition, and various components of physical fitness were measured in 940 children (aged 8.98 ± 3.39). The sports participation and confounding variables, such as parents' education and body weight as well as parents' sports activities, were estimated through a questionnaire completed by parents. In order to achieve the study purpose, the study used the multinomial logistic regression analysis and the multivariate analysis of covariance (MANCOVA). Results. Less-than-once-a-week sports participation was established in 41.1% of the children, once or twice a week - in 48.4%, and more often - in 10.5%. Obesity was established in 38.1% of the children. Children that had organized sports activity 1-2 times a week or more often showed a higher physical fitness level. Conclusions. Even though causality cannot be established, facilitation of organized sports activities may be a crucial aspect in public health efforts addressing the growing problems associated with overweight and obesity.